PERCEPTION OF RESIDENTS TOWARDS COMMUNITY TOURISM IMPACTS: A CASE STUDY AT MOUNT LAVINIA, SRI LANKA - Madawala, Kalani H. (Department of Economics, Faculty of Arts, University of Colombo, 2017)
This study has found the perceptions of the local community towards the developments in tourism and their perceptions towards the community tourism impacts. The host population was taken from the Mount Lavinia, Sri Lanka and 120 questionnaires were distributed. And the direct observations of the researcher have also included. The respondents of the study can be divided into mainly two parts. They are: The community with tourism income in their household and the community who has not engage in tourism income generation activity. Most of the community at Mount Lavinia who were not engage in tourism agreed that there are so many negative impacts of tourism while the community who engage in tourism were not concern much about the negativity that bring through tourism to their lives. The researcher has suggested that local governments and tourism promoters should pay particular emphasis to the residents to feel that their concerns are being considered, then they will support tourism.
Keywords: Tourism, Perception, Impacts, Residents